Effects of Supervision on Financial Stability and Performance of Insurance Companies in Nigeria: Array - Boloupremo, Tarila; Ogege, Samson (Acta Universitatis Danubius. Œconomica, 2021)
The paper examines the influence of supervision on financial stability and profit performance of insurance firms in Nigeria. Time series data spanning from 2011 – 2017 were sourced from structured research questionnaires, financial reports, industry reports, and the Nigerian insurers association (NIA) Digests. The data collected were analyzed using correlation matrix and regression analysis (OLS technique). Results from the data analyzed suggests that Insurance supervision significantly influences profit performance. Based on these findings, it is therefore recommended that Nigeria’s insurance regulatory agency should strengthen insurance operational guidelines issued to insurance firms via the execution of efficient and effective enforcement strategies.